Investigation of structural, magnetic and dielectric properties of SrM/PEEK: A potential microwave absorber. Issue 5 (1st March 2023) - Piracha, M.I.; Murtaza, G.; Nazir, Ghazanfar; Zelai, Taharh; Aloufi, Nuriyah Mohammed; Hassan, M.; Alshahrani, Thamraa; Abd-Rabboh, Hisham S.M.
Abstract: The current study aims to investigate the effect of Polyether Ether Ketone (PEEK) on the structural, magnetic, and microwave properties of substituted M-type SrFe11.5 Co0.5 O12 (SrM) hexaferrite. Nanocomposites based on SrM/PEEK in ratios 4:0, 3:1, 2:2, and 0:4 were prepared by employing the micro-emulsion method. The composites were further characterized using XRD, SEM, FTIR, and VNA. XRD results exhibited a single-phase hexaferrite structure with an average crystallite size of 40 nm for pure SrM, which decreased due to increasing PEEK concentration. FESEM micrographs revealed the surface morphology and nature of the grains in the prepared nanocomposites. EDAX plots showed the presence of the constituent elements e.g., Fe, Sr, C, and O, at the respective standard energies. VSM results revealed the diamagnetic and ferromagnetic nature of PEEK and pure SrM/nanocomposite samples, respectively. FTIR spectra of SrM depicted the formation of hexaferrite due to the presence of Fe–O stretching peak at 525 cm −1 . Reflection loss was found to decrease due to increasing ferrite concentration in PEEK. This indicates that SrM/PEEK composites are potential microwave absorbers for microwave applications in the X band.